INFORMATION AND COMMUNICATION TECHNOLOGIES IN SCHOOL LIBRARIES: in search of a dynamic area - Catini Lanzi, Lucirene Andrea; Vidotti, Silvana Aparecida Borsetti Gregorio; Ferneda, Edberto [UNESP] (Univ Federal Campina Grande, 2014)
The Information and Communication Technologies (ICT) can be combined with the acquisition of academic knowledge and cultural development of students, as they improve their information literacy, and why not say, also digital. Weaim in this research seek references and present experiences that encourage a new concept of school library with the use of ICT in teaching and learning in individual and collective development of the student community. To complement this study we prioritized the following objectives: to insert the technology into the routine of a school library; identify the informational and technological profile of adolescents; understand the needs and technological resources they use to obtain information in daily life and also analyze the importance the effective participation of the school library in the educational context of the school, through greater interaction between the librarian, teacher and pedagogical coordination seeking a cooperative and informal ICT teaching and learning for along with the students, sharing the search for information and knowledge, in a conscious and responsible way. Chosen as theoretical foundation the cognitive studies of Jean Piaget, witch explains how the stages of assimilation and accommodation of knowledge in cooperative practices work. As a methodology was developed a participatory-action research, to learn the behavioral state of young people and adolescents, based on the model of information search for the everyday life (Everyday Life Information Seeking) - ELIS, developed by Finnish researcher Savoleinen (2006), as well as identify the informational and technological profile of adolescents from two selected approaches in the scientific literature (HUGUES-HASSEL; AGOSTO, 2007; UCL, 2008). Thus, came up the initiative to create a Confraternity of the Library in a collaborative digital environment, providing the participants discussion and learning technologies as well as digital information literacy enhancement.
Keywords: SchoolLibrary; Information Technologies and Communication; Learning; Collaborative digital environments